2017
DOI: 10.1186/s12886-017-0461-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression profile in HLE B-3 cells during TGF-β2-induced epithelial-mesenchymal transition

Abstract: BackgroundRecent evidence has shown that long noncoding RNAs (lncRNAs) are involved in the process of epithelial-mesenchymal transition (EMT). However, little research has focused on the expression profile of lncRNAs during EMT in human lens epithelial cells (LECs) and their functions have not yet been described.MethodsDysregulated lncRNAs and mRNAs in normal human lens epithelial B-3(HLE B-3) cells and during transforming growth factor β2(TGF-β2)-induced EMT were analyzed via lncRNA microarray. Gene Ontology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The procedure was carried out as previously described ( 12 ). Briefly, the collected cataract tissues were treated orderly: 4% paraformaldehyde fixation, paraffin-embedding, section (4 µm thickness), deparaffinization, a descending series of 100, 95, 80 and 70% alcohol were applied for rehydration followed by 3% hydrogen peroxide incubation for 10 min, antigen retrieval, blocking with 10% goat serum (BioWorld Technology, Inc., St. Louis Park, MN, USA), primary antibody incubation (rabbit anti-SMAD4 antibody; 1:100; cat.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was carried out as previously described ( 12 ). Briefly, the collected cataract tissues were treated orderly: 4% paraformaldehyde fixation, paraffin-embedding, section (4 µm thickness), deparaffinization, a descending series of 100, 95, 80 and 70% alcohol were applied for rehydration followed by 3% hydrogen peroxide incubation for 10 min, antigen retrieval, blocking with 10% goat serum (BioWorld Technology, Inc., St. Louis Park, MN, USA), primary antibody incubation (rabbit anti-SMAD4 antibody; 1:100; cat.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have suggested that the lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), located on chromosome 11q13, which is involved in the process of EMT in the cancer [8, 9]. Moreover, the emerging evidence has revealed a potential contribution of particular lncRNAs to the development of PCO [10, 11]. However, to the best of our knowledge, whether MALAT1 can regulate EMT of LECs and contribute to the pathogenesis of PCO has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies reveal that the dysregulation of lncRNAs are impact the development and progression of cataract [31] [32] [33] [34] [35]. Compared with transparent lenses, KCNQ1OT1, TUG1, and H19 has identified to have signifi-cantly increased expression in age-related cataract [36] [37] [38].…”
Section: The Expression and Function Of Lncrnas In The Cataractmentioning
confidence: 99%